2016
DOI: 10.1189/jlb.1a0215-068rr
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 4 (IRF4) controls myeloid-derived suppressor cell (MDSC) differentiation and function

Abstract: Myeloid-derived suppressor cells (MDSCs) are immature cells that do not differentiate into mature myeloid cells. Two major populations of PMN-MDSCs (Ly6GLy6CGr1CD11b) and MO-MDSCs (Ly6GLy6CGr-1CD11b) have an immune suppressive function. Interferon regulatory factor 4 (IRF4) has a role in the negative regulation of TLR signaling and is associated with lymphoid cell development. However, the roles of IRF4 in myeloid cell differentiation are unclear. In this study, we found that IRF4 expression was remarkably sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 61 publications
5
43
2
Order By: Relevance
“…However, if sGP is given during the polarization of M1 macrophages then the production of IL-10 is significantly decreased. This could possibly be due to the activity of some sGP-mediated activation of a regulatory adaptor protein such as interferon regulatory factor-4 (IRF4), which has a profound inhibitory effect on proinflammatory cytokine production [29], but a milder inhibitory effect on IL-10 production [30,31]. The fact that sGP only interferes with the IL-10 production if given during the polarization step could be due to a role of a regulatory protein such as IRF-4 in the differentiation process of hematopoietic stem cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if sGP is given during the polarization of M1 macrophages then the production of IL-10 is significantly decreased. This could possibly be due to the activity of some sGP-mediated activation of a regulatory adaptor protein such as interferon regulatory factor-4 (IRF4), which has a profound inhibitory effect on proinflammatory cytokine production [29], but a milder inhibitory effect on IL-10 production [30,31]. The fact that sGP only interferes with the IL-10 production if given during the polarization step could be due to a role of a regulatory protein such as IRF-4 in the differentiation process of hematopoietic stem cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly be due to the activity of some sGP-mediated activation of a regulatory adaptor protein such as interferon regulatory factor-4 (IRF4), which has a profound inhibitory effect on proinflammatory cytokine production [29], but a milder inhibitory effect on IL-10 production [30,31]. The fact that sGP only interferes with the IL-10 production if given during the polarization step could be due to a role of a regulatory protein such as IRF-4 in the differentiation process of hematopoietic stem cells [31]. IRF-4 has been previously shown to be a target of viral processes to suppress the immune response and promote viral pathogenesis [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Since MDSCs are one of the key immunosuppressive cells involved in maintaining the tumor microenvironment in each skin cancers, abrogation of the suppressive function of MDSCs delays tumor growth in skin cancers. For example, Nam et al reported the significance of IFN regulatory factor (IRF)4 for the functional differentiation of MDSCs by myeloid-specific deletion of IRF4 to abrogate the inhibitory effects of MDSCs in suppressing T-cell proliferation [69]. More recently, Pan et al reported that increased expression of ten-eleven translocation-2 (tet2) on tumor-infiltrating myeloid cells maintained the suppressive function of immature myeloid cells through IL-1R/MyD88 pathways in melanoma patients [70].…”
Section: Mdscs As a Target For Immunotherapymentioning
confidence: 99%
“…MDSCs are potent inducers of immunosenescence [119], sepsis-acquired immunodeficiency [120] as well as cancer metastasis and progression [121]. MDSC are positively correlated with IL-6 and negatively correlated with IFN-ϒ [122,123].…”
Section: Clinical Features Of Viral Infection In Elderlymentioning
confidence: 99%